BIOTECHNOLOGICAL SYSTEM FOR THE SEARCH OF SUBSTANCES WITH POTENTIAL ACTIVITY AGAINST CORONAVIRUS - M.P. Smetiukh; O.P. Trokhimenko; S.O. Soloviov; I.V. Dziublyk; O.A. Kamatskyi; I.V. Savchuk; N.A. Bobyr (Biotechnologia Acta)
Aim. Development of a biotechnological system based on a non-pathogenic coronavirus strain for humans and a sensitive cell line to the selected strain aimed at identifying compounds with potential antiviral activity.